Thermally Triggered Interface for Simplified Organic Solar Cells - Suwapat Kongsabay; Gilles Henri Roche; Olivier Dautel; Vinich Promarak; Guillaume Wantz (Advanced Photonics Research)
Organic photovoltaic (OPV) cells are commonly produced by successive printing of four layers on top of a transparent conducting electrode, with the active layer sandwiched in between interlayers followed by the top electrode. Here, the simplification of OPV manufacturing without the need to coat a hole transport layer (HTL) in inverted OPV (n–i–p) is reported. To ensure the required hole selectivity, thermally trigged molecules are directly blended in the active layer during device casting. Following thermal annealing of the complete devices, organosulfur molecules self‐assembled to form a hole–transporting interface between the silver top electrode and the active layer, thereby enabling working devices. Device optimization is performed by varying the concentration of these molecules and the thermal annealing conditions. The performances of the simplified devices approach those of control devices with vacuum‐evaporated MoO3 HTLs. The solar cells exhibit very encouraging thermal and photostabilities. This work opens the route to high efficiency, simplified, and low‐cost organic solar cells.